Classical tautology versus quantum mechanical contradiction - Toh, Sing Poh; Zainuddin, Hishamuddin (2005)
This is a pedagogical note introducing the basic idea of contextuality through a pairof spin- 1/2 particles system, quantum mechanically interpreting Schütte’s tautology, and using the later to generate a set of uncolourable rays in three-dimensional Hilbert space in order to prove Kochen-Specker Theorem.